Dot-ELISA for the diagnosis of neurocysticercosis Dot-ELISA no diagnóstico da neurocisticercose - Rakhi Biswas; S.C. Parija; S.K. Narayan (Revista do Instituto de Medicina Tropical de São Paulo, 2004)
The aim of the present study was to standardize and evaluate dot-Enzyme linked immunosorbent assay (Dot-ELISA), a simple and rapid test for the detection of cysticercus antibodies in the serum for the diagnosis of neurocysticercosis (NCC). The antigen used in the study was a complete homogenate of Cysticercus cellulosae cysts obtained from infected pigs and dotted on to nitrocellulose membrane. Test sera were collected from the patients of NCC, and control sera from patients with other diseases and healthy students and blood donors of the Jawaharlal Institute of Postgraduate Medical Education and Research (JIPMER) Hospital, Pondicherry, during a study period from 2001 to 2003. Dot-ELISA detected antibodies in 14 of 25 (56%) in clinically suspected cases of NCC, 13 of 23 (56.5%) in CT/MRI proven cases of NCC and 2 of 25 (8%) each in non-cysticercal CNS infection controls and healthy controls. The test showed a sensitivity of 56.25%, specificity of 92%, positive predictive value of 87.09%, and negative predictive value of 70.76%. Results of the present study shows that the Dot-ELISA as a simple test can be used in the field or poorly equipped laboratories for diagnosis of NCC . O objetivo do presente estudo foi estandardizar e avaliar o Dot-ELISA, um teste simples e rápido para detectar anticorpos de cisticercos no soro para diagnóstico da neurocisticercose (NCC). O antígeno usado no estudo foi um homogenizado completo de cistos de Cysticercus cellulosae obtidos de porcos infectados e marcados sobre a membrana de nitrocelulose. Os soros testados foram coletados de pacientes com NCC e os soros controle de pacientes com outras doenças e estudantes saudáveis e doadores e sangue do "Jawaharlal Institute of Postgraduate Medical Education and Research Hospital", em Pondicherry, durante o período de estudo de 2001 a 2003. Dot-Elisa detectou anticorpos em 14 de 25 (56%) casos suspeitos de NCC, em 13 de 23 (56,5%) em CT/MRI casos provados de NCC e em 2 de 25 (8%) cada em controles de infecções do sistema nervoso não ...